Utilization of Social Media in Marketing Tourist Destinations in Indonesia - Dharmawan, Rifky; Nur, Siti Utami Novia; Karimah, Hapsyah Nur; Lestari, Rahayu; Hardini, Resti; Digdowiseiso , Kumba (CV ODIS, 2023)
The progress of the times requires every individual and organization to keep pace. In business, it cannot be separated from marketing which is closely related to sales. Technology that is currently very developed can be used as a means of marketing, for example, social media. Besides being able to advertise for free on social media, the reach of social media is also very wide. In the tourism sector, the perceived benefits of marketing through social media are the knowledge of tourist attractions by many people, thus affecting tourism demand. The purpose of this study is to review and analyze the relevance of social media in terms of marketing, and how much impact social media has on the tourism sector. The research method used is a review of literature studies with conceptual review techniques. In this research, the literature analysis process was carried out by collecting data in the form of relevant scientific articles sourced from Google Scholar published between 2019 and 2023. Furthermore, Vosviewer is used to visualize the most important topics in this subject